The Effect of Financial Literacy on Access to Credit for Maize Farmers in Madura Island, Indonesia - Puteri Nanda Nuriyantika Agustin; Dian Eswin Wijayanti; Mardiyah Hayati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The level of financial literacy affects the access to credit that is appropriate in overcoming the finances of corn farmers on Madura Island. The purpose of this study is to determine the effect of financial literacy on access to credit for corn farmers on Madura Island. The method used in this research is quantitative with probit regression analysis tool to determine the relationship between the influence of the independent variable of financial literacy on the dependent variable of credit access. The data used in this study is primary data, namely data obtained directly by interviews with 143 corn farmers on Madura Island. The results showed that financial literacy influences corn farmers' credit access, but financial literacy needs to be improved for better and more appropriate credit access. Increasing financial literacy can be done with financial training to improve the welfare of corn farmers in Madura.